Pengaruh Warna Umpan Terhadap Hasil Tangkapan Ikan Pada Alat Tangkap Pancing Di Desa Bletok Situbondo - Rijal, Mohammad Syaifur; Silviyanti, Nurul Amalia; Handayani, Creani (Program Studi Teknik Kelautan Universitas Abdurachman Saleh Situbondo, 2024)
In Bletok Village, Bungatan District, Situbondo Regency, there is hand line fishing equipment. Usually, hand-line fishermen use live bait. But getting live bait is quite difficult and the price is also quite expensive. To overcome this problem, fishermen usually use artificial bait, namely chicken feathers. This study was conducted in Bletok Village, Bungatan District, Situbondo Regency, East Java for one month from January to February. This research aims to determine catch results and the influence of bait color on handline fishing gear. The method used in this research is experimental fishing, namely carrying out fishing operations using treated hand lines. The bait colors tested were red, white and black chicken feathers. Then the data obtained was processed using SPSS using the Kolmogorov-Smirnov test and ANNOVA test. The catches from Ulur fishing rods during the research were Yellow Selar Fish (Selaroides leptolepis), Fly Fish (Layang Perkak), Bentong Selar Fish (Crumenophthalmus), Mackerel Fish (Rastrelliger sp), Pompano Fish (Carangodes) and Tuna Fish (Sarda orientalis). From the results of the ANNOVA test, it is stated that F count > F table with F count 1.186 F table 3.95, meaning that H0 is rejected, so it can be said that the difference in bait color has no real effect on fishermen's catche